Framework for guiding the design of mobile collocated interaction - Zee, Jasmine Wei Li (2022)

(untitled)
The physical existence of collaborative activities can be improved with mobile application. Collaborative activities of “same time, same place” has the same meaning of collocated interactions. While collaborative activities requires trusts, and social interaction, this paper aim to research on improving collaborative interactions with mobile collocated applications and propose a mobile collocated interactions guided design framework. The proposed attributes were based on past literature review and the proposed mobile collocated interactions guided framework were generated. The prototype of mobile collocated applications was created based on the proposed attributes and framework with the food ordering menu scenarios in a restaurant. The qualitative method was used through user interview survey, whereby the prototype was introduced and experimented by the users. The results were interpreted with positive feedback of having mobile collocated application of food menu ordering application whereby there are multiple functions related to collocated activites were introduces such as view your menu, table chat request, and able to view multipleusers in which these functions are not yet seen in the current/traditional food ordering menu applications.